Residue soil modifier for shield construction and settlement control method thereof

Through technical means such as modified polyacrylamide cross-linking with dihydrodehydrodipine alcohol and precise pressure maintenance of soil warehouses, the problem of spraying and mud cakes in shield construction under complex geological conditions was solved, and the problem of shield structure construction was achieved. The stability and shear strength of the slag are improved, as well as the micro-segregation control during shield construction.

CN119410370AInactive Publication Date: 2025-02-11CHINA POWER CONSTR CHENGDU CONSTR INVESTMENT CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510020031.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Shield construction is prone to problems such as gushing and mud cake formation under complex geological conditions such as water-rich sand layers and mudstone formations, resulting in increased engineering difficulty and increased risk of ground settlement.

Method used

The modified polyacrylamide, foam agent and water are used as the slag modified agent, and the adhesion and stability of the slag is enhanced by partially hydrolyzed polyacrylamide and dihydrodehydrogenated dicyanol. The physical properties of the slag are adjusted by the uniform distribution of the modified polyacrylamide in low concentrations. At the same time, the method of precise pressure maintenance of soil warehouses, sludge injection in Zhongdun, synchronous thickening plastic double slurry and multi-sequence slurry replenishment is adopted to achieve micro-segmentation control during shield construction.

Benefits of technology

It effectively prevents the occurrence of gushing and mud cakes, improves the overall stability and shear strength of the residue, reduces the risk of ground settlement, and realizes micro-deformation control during shield construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410370A_ABST
    Figure CN119410370A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of muck improvement, in particular to a muck improver for shield construction and a settlement control method thereof, and the muck improver comprises the following components: 50-100 parts by weight of modified polyacrylamide, 0.4-0.6 part by weight of a foaming agent and 800-1000 parts by weight of water; wherein the modified polyacrylamide is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydrodiconiferyl alcohol according to a mass ratio of 1: (0.3-0.7); partially hydrolyzed polyacrylamide and dihydrodehydrodiconiferyl alcohol are cross-linked, the water retention rate of the muck is increased through hydrophilic groups, the permeability of the muck is reduced by utilizing a net structure, the muck modifier is obtained by mixing a low-concentration modified polyacrylamide aqueous solution and a foaming agent, uniform distribution in the muck is adjusted, and the muck modifier has the advantages that the muck modifier can be used for improving the muck permeability. And meanwhile, the balance technologies of soil bin precise pressure maintaining, middle shield mud injection, synchronous thickening plastic double-liquid slurry injection and multi-sequence slurry supplementing are combined, and micro-settlement control in the shield construction process is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of slag improvement, in particular to a slag improver for shield construction and a settlement control method thereof. Background Art

[0002] Earth Pressure Balance Shield construction is an advanced technology widely used in underground engineering construction such as subways and tunnels. Earth Pressure Balance Shield is referred to as EPB Shield. It is a mechanical shield. By setting a partition at the front of the shield machine, the soil bin and the screw conveyor for soil discharge are filled with cut soil. The thrust of the propulsion jack is used to pressurize the excavated soil in the soil bin, so that the soil pressure acts on the excavation surface to maintain its stability. The supporting material of this shield is mainly the soil itself. Its structure includes shield shell, cutter head, cutter head drive, screw conveyor, etc. , belt conveyor, segment installation machine, man bin, hydraulic system and other key components. The working principle of the earth pressure balance shield is as follows: the cutter disc at the front end of the shield machine rotates to cut the soil on the excavation surface, and the cut soil enters the soil bin through the cutter disc opening. When the soil fills the soil bin, the passive earth pressure and the earth pressure and water pressure on the excavation face reach a basic balance, so that the excavation face and the shield face are in a stable state. Subsequently, the screw conveyor transports the soil from the soil bin to the belt conveyor, and then the belt conveyor transports the soil to the slag truck parked on the track.

[0003] When the shield passes through complex geological conditions such as water-rich sand layers and mudstone formations, it often faces complex engineering problems. When the water-rich sand layer has a high content, "eruption" is prone to occur, and when the mudstone formation has a high content, mud cake is prone to occur. In view of this, we propose a slag improver for shield construction and its settlement control method. Summary of the invention

[0004] The object of the present invention is to provide a slag improver for shield construction and a settlement control method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides a slag improver for shield construction, comprising the following components: 50-100 parts by weight of modified polyacrylamide, 0.4-0.6 parts by weight of foaming agent and 800-1000 parts by weight of water; The modified polyacrylamide is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 1:0.3-0.7.

[0006] Preferably, the preparation method of the modified polyacrylamide is as follows: The partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol are dissolved in dimethyl sulfoxide respectively, and stirred until completely dissolved to form a uniform solution. In the solution containing the partially hydrolyzed polyacrylamide, the pH value is adjusted to 6-7, and a catalyst p-toluenesulfonic acid is added, and then N,N'-carbonyldiimidazole is added. After stirring evenly, the solution containing dihydrodehydroconiferyl alcohol is added to the solution containing the partially hydrolyzed polyacrylamide, and stirring is continued. At 40-60°C, stirring is continued and the constant temperature is maintained for 4-8h. The mixed solution after the reaction is poured into a large amount of deionized water, filtered, washed and dried to obtain modified polyacrylamide.

[0007] Partially hydrolyzed polyacrylamide is a long-chain polymer and a type of anionic polyacrylamide. Dihydrodehydroconiferyl alcohol contains multiple hydroxyl groups, which can react with the carboxyl groups on the partially hydrolyzed polyacrylamide to form covalent bonds, thereby achieving cross-linking. The cross-linked product formed by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol can further enhance the adhesion to the slag, thereby improving the overall stability and shear strength of the slag, helping to maintain the soil pressure balance in front of the shield machine and reducing the risk of ground subsidence. At the same time, the hydroxyl groups in dihydrodehydroconiferyl alcohol have good water absorption and water retention capacity, which can effectively reduce the loss of water from the slag and maintain an appropriate moisture content, which is beneficial to controlling the mud properties during shield construction. It avoids hardening and agglomeration caused by drying, making the slag easier to be cut and discharged by the shield machine, reducing the risk of mud cake, and the higher water absorption and water retention capacity can effectively absorb the free water in the slag to form a stable colloidal structure, thereby enhancing the slag's resistance to water dispersion; in addition, the three-dimensional network structure formed by the cross-linked product can effectively fill the gaps in the slag, reduce the ability of water molecules to pass through, thereby reducing the permeability of the slag, and reducing the possibility of groundwater flowing into the tunnel through the slag, thereby effectively preventing the occurrence of gushing; finally, the natural product dihydrodehydroconiferyl alcohol is selected to replace part of the chemical synthetic material cross-linking agent, which can reduce the potential impact on the environment while maintaining a good improvement effect.

[0008] Preferably, the mass concentration of the solution containing partially hydrolyzed polyacrylamide is 5-10%, and the mass concentration of the solution containing dihydrodehydrodisinopyrrolidone is 1-4%.

[0009] Preferably, the mass fraction of the toluenesulfonic acid in the solution containing partially hydrolyzed polyacrylamide is 0.1-0.5%, and the mass fraction of the N,N'-carbonyldiimidazole in the solution containing partially hydrolyzed polyacrylamide is 1-2%.

[0010] Preferably, the partially hydrolyzed polyacrylamide has a degree of hydrolysis of 35-40% and a molecular weight of 12-16 million.

[0011] Preferably, the slag conditioner is prepared by mixing a foaming agent with a low concentration modified polyacrylamide solution, wherein the foaming agent is mixed with a modified polyacrylamide solution with a mass fraction of 5-10% in a mass ratio of 0.4-0.6:1000, and the optimal slump of the slag conditioner is 10-15 cm.

[0012] Choosing a low concentration of modified polyacrylamide solution can maintain the appropriate fluidity of the slag while ensuring the improvement effect, avoiding the slag from clogging the pipeline during transportation, affecting the normal operation of the shield machine, and increasing the wear and maintenance costs of the equipment. In addition, a lower concentration of modified polyacrylamide can be more evenly distributed in the slag, thereby better adjusting the physical properties of the slag. In addition, a lower concentration of modified polyacrylamide can reduce the use of chemical substances and reduce the impact on the environment.

[0013] Preferably, the injected volume of the soil conditioner accounts for 1-3% of the volume of the different geological soils to be improved, and the different geological soils to be improved are one or more of pure sand formations, sand and gravel formations, mudstone formations and composite formations.

[0014] On the other hand, the present invention provides a method for controlling the settlement of a slag improver for shield construction, which is used for a slag improver for shield construction as described in any one of the above, comprising the following steps: Slag improvement: According to geological conditions and test data, adjust the proportion of components in the slag improver, inject the prepared slag improver into the front of the shield machine cutter head and the soil bin through a plunger pump, and the slag improver and slag are fully mixed under the action of the cutter head rotation and the screw conveyor to improve the slag performance; Precise pressure maintenance in soil bin: Use sensors to monitor pressure changes in the soil bin in real time, and dynamically adjust the pressure in the soil bin according to the shape of the excavation surface and the characteristics of the stratum to ensure that it remains between the active balance pressure and the passive balance pressure; Middle shield mud injection: During the shield tunneling process, start the mud injection pump to inject plastic mud into the gap between the shield and the excavation surface. To prevent the loss of plastic mud, keep the pressure difference between the synchronous grouting pressure and the soil bin pressure below 0.15MPa; Synchronous injection of thickened plastic dual-liquid slurry: During the shield tunneling process, the dual-liquid slurry grouting pump is started to inject thickened plastic dual-liquid slurry into the gap between the segment and the stratum; Multi-sequence grouting: grouting is carried out every 12-24 hours after the installation of the pipe segment. The grouting locations are the gaps left after the initial construction and the unsatisfactory areas caused by water loss during the solidification process of the synchronous thickening plastic double liquid slurry. The grouting ratio is a water-cement ratio of 1:0.5~1, and the grouting pressure is 3-4bar.

[0015] The method of improving slag soil by adding foam and low-concentration modified polyacrylamide can achieve an ideal slag soil state to prevent gushing and mud cake, and is more suitable for pressure-maintaining excavation; the use of precise pressure maintenance in the soil bin, mud injection in the middle shield, simultaneous injection of thickened plastic double-liquid slurry and multi-sequence grouting achieves the full-process balance of the shield excavation face, the balance above the shield body, the balance behind the shield tail and the balance behind the segment wall, and can achieve micro-deformation control in shield construction; precise pressure maintenance in the soil bin is based on the characteristics of the current peripheral arc-shaped cutter head excavation face, and it is proposed that the soil bin pressure at each point on the excavation face should be between the active balance pressure and the passive balance pressure, so that the stratum above the shield cutter head excavation face is zero-deformed; mud injection in the middle shield is synchronously injected between the shield excavation forming surface and the outer surface of the shield body as the shield advances. Plastic mud is injected into the gaps between the shield and the excavation surface to achieve a balance between the shield body and the excavation forming surface, which can reduce the settlement of the stratum above the shield body and solve the problems of synchronous slurry loss to the soil bin, shield body being wrapped by synchronous slurry, and shield tunneling gushing; simultaneous injection of thickened plastic double-liquid slurry solves the shield construction problems of segment floating, synchronous slurry easy loss to the soil bin, and synchronous slurry volume reduction due to water loss; multi-sequence grouting (supplementing grouting behind the segment wall at intervals, and implementing it multiple times) is to solve the problem of surface settlement caused by the reduction of water volume during the solidification process of the synchronous slurry, and fill the volume reduction problem caused by the water loss of the synchronous slurry through multi-sequence grouting; the above measures solve the time and space balance problems of shield construction, and can achieve micro-deformation or even zero deformation control.

[0016] Preferably, the plastic mud is prepared from calcium-based bentonite: water: water glass in a mass ratio of 15-20:10-15:1.

[0017] Preferably, the thickened plastic two-liquid slurry is prepared by mixing liquid A and liquid B in a volume ratio of 10:1-3, wherein liquid A is prepared from 150-200 parts by weight of cement, 350-400 parts by weight of fly ash, 650-700 parts by weight of dry fine sand, 50-100 parts by weight of sodium bentonite and 400-450 parts by weight of water, and liquid B is prepared by mixing 5-6 parts by weight of polyacrylamide and 994-995 parts by weight of water.

[0018] Compared with the prior art, the present invention has the following beneficial effects: In the slag improver and settlement control method for shield construction, a cross-linking reaction of partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol is used to further enhance the bonding force to the slag, thereby improving the overall stability and shear strength of the slag, and the water retention rate of the slag is improved through the hydrophilic group of the product, and the network structure formed by the cross-linked product is used to reduce the permeability of the slag, and the slag improver is obtained by mixing a low-concentration modified polyacrylamide aqueous solution with a foaming agent, and the uniform distribution in the slag is adjusted. At the same time, combined with the balance technology of precise pressure maintenance in the soil bin, mud injection in the middle shield, simultaneous injection of thickened plastic double liquid slurry, and multi-sequence grouting, the problems of gushing, mud cake formation, floating of pipe segments, and surface settlement in shield construction are solved, and micro-settlement control in the shield construction process is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the shear strength variation curve of the slag improver of Example 1 of the present invention and Comparative Examples 1-3 under pure sand formation; Figure 2 The internal friction angle curves of the slag improvers of Example 1 of the present invention and Comparative Examples 1-3 under pure sand formation; Figure 3 The moisture content curves of the slag improvers of Example 1 and Comparative Examples 1-3 after pressurization under pure sand formation; Figure 4 The slag residual rate curves of the slag improvers of Example 1 of the present invention and Comparative Examples 1-3 under pure sand formation. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] See also Figure 1-4 As shown, a slag improver for shield construction of the present invention comprises the following components: 50-100 parts by weight of modified polyacrylamide, 0.4-0.6 parts by weight of foaming agent and 800-1000 parts by weight of water; The modified polyacrylamide is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 1:0.3-0.7.

[0022] The different geological slag soils to be improved are one or more of pure sand strata, sand and gravel strata, mudstone strata and composite strata.

[0023] Embodiment 1: A slag improver for shield construction and a method for controlling its settlement, comprising the following steps: Prepare components: 75 parts by weight of modified polyacrylamide, 0.5 parts by weight of foaming agent and 1000 parts by weight of water; the different geological slag to be improved is a pure sand stratum; The modified polyacrylamide is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 1:0.5. The slag improver is prepared by mixing a foaming agent and a modified polyacrylamide solution with a mass fraction of 7.5% at a mass ratio of 0.5:1000; the injection volume of the slag improver accounts for 3% of the volume of the different geological slag to be improved; the hydrolysis degree of the partially hydrolyzed polyacrylamide is 40%, and the molecular weight is 16 million; The plastic mud is prepared by mixing calcium-based bentonite: water: water glass in a mass ratio of 15:12:1; the thickened plastic double-liquid slurry is prepared by mixing liquid A and liquid B in a volume ratio of 10:1, wherein the liquid A is prepared by mixing 200 parts by weight of cement, 400 parts by weight of fly ash, 700 parts by weight of dry fine sand, 100 parts by weight of sodium-based bentonite and 420 parts by weight of water, and the liquid B is prepared by mixing 5 parts by weight of polyacrylamide and 995 parts by weight of water; Dissolve partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in dimethyl sulfoxide respectively, stir until completely dissolved to form a uniform solution, adjust the pH value to 7 in the partially hydrolyzed polyacrylamide solution with a mass concentration of 10%, add p-toluenesulfonic acid as a catalyst, wherein the mass fraction of toluenesulfonic acid in the partially hydrolyzed polyacrylamide solution is 0.5%, then add N,N'-carbonyldiimidazole, wherein the mass fraction of N,N'-carbonyldiimidazole in the partially hydrolyzed polyacrylamide solution is 1%, stir evenly, add the dihydrodehydroconiferyl alcohol solution with a mass concentration of 3% to the partially hydrolyzed polyacrylamide solution, and continue stirring, continue stirring and keep the constant temperature at 60°C for 6h, pour the mixed solution after the reaction into a large amount of deionized water, filter, wash and dry to obtain modified polyacrylamide; Slag improvement: According to geological conditions and test data, adjust the proportion of components in the slag improver, inject the prepared slag improver into the front of the shield machine cutter head and the soil bin through a plunger pump, and the slag improver and slag are fully mixed under the action of the cutter head rotation and the screw conveyor to improve the slag performance; Precise pressure maintenance in soil bin: Use sensors to monitor pressure changes in the soil bin in real time, and dynamically adjust the pressure in the soil bin according to the shape of the excavation surface and the characteristics of the stratum to ensure that it remains between the active balance pressure and the passive balance pressure; Middle shield mud injection: During the shield tunneling process, start the mud injection pump to inject plastic mud into the gap formed by the shield body and the excavation forming surface. To prevent the loss of plastic mud, keep the pressure difference between the synchronous grouting pressure and the soil bin pressure below 0.15MPa; Synchronous injection of thickened plastic dual-liquid slurry: During the shield tunneling process, the dual-liquid slurry grouting pump is started to inject thickened plastic dual-liquid slurry into the gap between the segment and the stratum; Multi-sequence grouting: grouting is carried out every 24 hours after the installation of the segments. The grouting locations are the gaps left after the initial construction and the unfilled areas caused by water loss during the solidification process of the synchronous thickening plastic double liquid slurry. The grouting ratio is a water-cement ratio of 1:1, and the grouting pressure is 4 bar.

[0024] Embodiment 2: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The modified polyacrylamide is 100 parts by weight, and the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 1:0.5. The slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and other conditions remain unchanged.

[0025] Embodiment 3: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The modified polyacrylamide is 100 parts by weight, and the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.7. The slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and the other conditions remain unchanged.

[0026] Embodiment 4: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag soils to be improved are sandy and gravel strata, 50 parts by weight of modified polyacrylamide, which is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.5, and the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 5%, and the other conditions remain unchanged.

[0027] Embodiment 5: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag soils to be improved are sandy and gravel strata, 100 parts by weight of modified polyacrylamide, which is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.5, and the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and other conditions remain unchanged.

[0028] Embodiment 6: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag soils to be improved are sandy and gravel strata, 100 parts by weight of modified polyacrylamide, which is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.7, and the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and other conditions remain unchanged.

[0029] Embodiment 7: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag to be improved is a mudstone formation, 75 parts by weight of modified polyacrylamide, which is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.3, and the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 7.5%, and the other conditions remain unchanged.

[0030] Embodiment 8: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag to be improved is a mudstone formation, 100 parts by weight of modified polyacrylamide, the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol at a mass ratio of 0.3, the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and the other conditions remain unchanged.

[0031] Embodiment 9: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slag to be improved is a mudstone formation, 100 parts by weight of modified polyacrylamide, the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.5, the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 10%, and the other conditions remain unchanged.

[0032] Embodiment 10: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slags to be improved are composite strata, 50 weight parts of modified polyacrylamide, the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol at a mass ratio of 0.3, the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 5%, and the other conditions remain unchanged.

[0033] Embodiment 11: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slags to be improved are composite strata, 50 weight parts of modified polyacrylamide, the modified polyacrylamide is modified by partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol at a mass ratio of 0.5, the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 5%, and the other conditions remain unchanged.

[0034] Embodiment 12: Compared with Embodiment 1, the difference between this embodiment and Embodiment 1 is that: The different geological slags to be improved are composite strata, 75 parts by weight of modified polyacrylamide, which is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 0.5, and the slag improver is prepared by mixing a foaming agent with a modified polyacrylamide solution with a mass fraction of 7.5%, and the other conditions remain unchanged.

[0035] Comparative Example 1: The method of Example 1 was adopted, and the partially hydrolyzed polyacrylamide was replaced by carboxymethyl cellulose.

[0036] Comparative Example 2: The method of Example 1 was adopted, and part of the hydrolyzed polyacrylamide was replaced with sodium bentonite slurry.

[0037] Comparative Example 3: The method of Example 1 was adopted, and the partially hydrolyzed polyacrylamide was replaced with a 5000 molecular weight sodium polyacrylate aqueous solution.

[0038] The present invention adopts a shield construction slag improver prepared by modified polyacrylamide, wherein the performance index inspection items and inspection standards of the shield construction slag improver are as follows: The shear strength is tested by direct shear test. By changing the applied pressure, the peak shear strength of the slag sample under different pressures is measured, and the internal friction angle is calculated. The internal friction angle refers to the friction between the slag particles, which determines the stability of the slag. An appropriate internal friction angle can ensure that the slag is neither too loose nor too tight, thereby maintaining the stability of the excavation surface. The specific test steps are: put the improved slag sample into the shear box, perform horizontal shear under a vertical pressure of 200kPa, record the shear force when it reaches failure, and then calculate the internal friction angle according to the Mohr-Coulomb criterion, tan(ϕ)=(τ f −c) / σ n , τ f is the maximum shear stress (i.e. shear strength) at failure; c is cohesion, which indicates the shear strength between soil particles due to cementation; σ n is the normal stress (perpendicular load) acting on the shear plane.

[0039] Permeability refers to the ability of slag to allow water to pass through. Low permeability helps prevent groundwater from entering the working face and reduce the risk of eruption. The permeability coefficient of the improved slag is measured by a constant head permeability test. The specific steps of the test are: first, fill the organic glass tube with improved slag with a cross-sectional area of ​​A and a length of L, open the water valve, and let the water flow through the sample from top to bottom. After the head difference Δh and the seepage flow rate Q are stable, measure the water flow rate V flowing through the sample within a fixed time t. The permeability coefficient is calculated according to the following formula: K=VL / AΔht, where K is the permeability coefficient cm / s; A is the cross-sectional area of ​​the organic glass tube cm 2 ; Δh is the head height difference in cm; t is the time in s; V is the water flow rate in cm flowing through the sample in time t 3 .

[0040] Water retention rate refers to the ability of soil to retain water. High water retention rate helps maintain the moisture of soil and avoid hardening caused by drying. It also reduces water loss and helps control the construction environment. The water retention rate is determined by the weight method. First, the mass of the improved soil sample in the dry state (m 1 ), soak the sample in water until it is saturated, take it out, absorb the excess water on the surface with filter paper, and weigh it immediately to obtain the mass of the sample in the saturated state (m 2 ), calculate the water retention rate (m 2 -m 1 ) / m 1 ×100%.

[0041] The water dispersibility of the slag improver is characterized by testing the mass residual rate of the slag. The higher the mass residual rate of the slag, the better its water dispersibility. Water is fed into the water inlet, and the flow meter controls the flow rate to be 10m / s. The modified slag is placed in the flowing water, and the discharged liquid is collected at the outlet to calculate the mass residual rate of the slag. The mass residual rate = (weight of the slag after treatment / weight of the slag before treatment) × 100%.

[0042] According to the above standards, a slag improver for shield construction prepared in the above Examples 1-12 and Comparative Examples 1-3 was tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-12 and Comparative Examples 1-3 Refer to the above data and attached Figure 1-4 , which fully shows that compared with Comparative Examples 1-3, Examples 1-12 can fully show the effect of modified polyacrylamide on the internal friction angle, permeability, water resistance and water retention performance of the slag in shield construction.

[0043] Since the present invention adopts modified polyacrylamide to prepare the slag improver, the performance of the slag improver is effectively improved by modifying the polyacrylamide, as follows: It can be seen from Examples 1-3 that in pure sand formations, with the continuous changes in the proportion of modified polyacrylamide components and the mass fraction of modified polyacrylamide solution in the slag improver, the improvement effect of the slag changes continuously. Since the pure sand formation has large particles, high porosity, and strong permeability, it is easy to cause soil erosion. In order to enhance the cohesion and stability of the slag, a certain fluidity must be maintained. Therefore, the use of a modified polyacrylamide solution with a mass fraction of 7.5% can provide sufficient viscosity and stability to prevent excessive water loss, while maintaining good fluidity. The cross-linking reaction of partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in modified polyacrylamide can improve the overall stability and shear strength of the slag. The water absorption and water retention capacity of the hydrophilic group can improve the water retention capacity of the slag. The cross-linked network structure can fill the gaps in the slag and reduce the permeability of the slag. However, when the content of dihydrodehydroconiferyl alcohol is too high, the degree of cross-linking will be too strong, making the modified polyacrylamide viscous and reducing its fluidity. Therefore, the best effect is achieved when the mass ratio of partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol is 1:0.5.

[0044] It can be seen from Examples 4-6 that in the gravel stratum, with the continuous changes in the proportion of modified polyacrylamide components and the mass fraction of the modified polyacrylamide solution in the slag conditioner, the improvement effect of the slag changes continuously. The gravel stratum contains more large particles, large pores, and extremely strong water permeability, and needs to maintain a high fluidity. Therefore, a modified polyacrylamide solution with a mass fraction of 5% is used. The lower mass fraction can increase the cohesion of the slag, reduce water loss, and improve the stability and plasticity of the slag without affecting the fluidity; in the modified polyacrylamide, the content of dihydrodehydrodisinopyrol increases, and the degree of cross-linking increases. When the degree of cross-linking is low, the stability brought by the cross-linking and the effect of improving the adhesion of the slag cannot be exerted, and when the degree of cross-linking is too high, the problem of pipeline blockage is prone to occur.

[0045] It can be seen from Examples 7-9 that in mudstone formations, with the continuous changes in the proportion of modified polyacrylamide components and the mass fraction of the modified polyacrylamide solution in the slag conditioner, the improvement effect of the slag changes continuously. The mudstone formation has fine particles, strong water absorption, and is easy to swell. Therefore, a modified polyacrylamide solution with a mass fraction of 10% is used. A higher mass fraction helps to form a more stable colloidal structure, effectively inhibit the expansibility of mudstone, reduce the impact on the shield machine, and improve the transportation performance of the slag; in the modified polyacrylamide, the content of dihydrodehydroconiferyl alcohol determines the cross-linking density of the modified polyacrylamide. If the cross-linking density is too high, it cannot be effectively and evenly distributed in the slag. If the cross-linking density is too low, the three-dimensional network structure cannot be used to fill the gaps in the slag, and the permeability is improved.

[0046] It can be seen from Examples 10-12 that in the composite stratum, with the continuous changes in the proportion of modified polyacrylamide components and the mass fraction of the modified polyacrylamide solution in the slag conditioner, the improvement effect of the slag changes continuously. The composite stratum is composed of a variety of geological materials, including sand, pebbles, clay, etc., and the geological conditions are complex and changeable. Therefore, the selection of a modified polyacrylamide solution with a mass fraction of 7.5% is a compromise choice, which aims to balance the improvement effect under various geological conditions, so that it can meet the coagulation requirements of large particles and adapt to the stability requirements of fine particles, ensuring the safety and efficiency of the overall construction process; in the modified polyacrylamide, the cross-linking of dihydrodehydroconiferyl alcohol and partially hydrolyzed polyacrylamide can bring hydrophilic groups, and the hydrophilic groups have good water absorption and water retention capacity. Therefore, when the content of dihydrodehydroconiferyl alcohol is low, the water retention will deteriorate, and the cross-linking structure is too strong, which will affect the fluidity of the modified polyacrylamide. Therefore, when the degree of cross-linking is moderate, various performances can be balanced.

[0047] According to the above test experiments, it can be known from Examples 1-3 that in pure sand formations, the slag improver for shield construction prepared in Example 1 has the best performance, and Example 1 is taken as the best example; By comparing Example 1 with Comparative Examples 1-3, it can be seen that: In Comparative Example 1, part of the hydrolyzed polyacrylamide is replaced by carboxymethyl cellulose, and the improvement effect of the slag is poor. This is because although carboxymethyl cellulose also has a certain viscosity, its viscosity is lower than that of the modified polyacrylamide solution, resulting in weak stability and cohesion in the slag, and it cannot provide sufficient supporting force. The modified polyacrylamide solution, due to the cross-linking effect of part of the hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol, can form a stable colloidal structure in the slag, enhance the cohesion and stability of the slag. Therefore, the improvement effect of the slag is worse when the part of the hydrolyzed polyacrylamide is replaced by carboxymethyl cellulose.

[0048] In Comparative Example 2, part of the hydrolyzed polyacrylamide is replaced with sodium-based bentonite slurry, and the improvement effect of the slag is poor. This is because although the sodium-based bentonite slurry also has a certain viscosity, its particles are large and uneven, and it is easy to form flocs, resulting in poor fluidity of the slurry. In addition, the swelling properties of the sodium-based bentonite will cause the viscosity of the slurry to be too high, affecting the propulsion efficiency of the shield machine. The modified polyacrylamide solution, under the action of dihydrodehydroconiferyl alcohol, can be effectively dispersed in water through its hydrophilic groups. Therefore, the part of the hydrolyzed polyacrylamide is replaced with sodium-based bentonite slurry, and the improvement effect of the slag becomes worse.

[0049] In Comparative Example 3, part of the hydrolyzed polyacrylamide is replaced by a 5000 molecular weight sodium polyacrylate aqueous solution, and the improvement effect of the slag is poor. This is because the molecular weight of 5000 molecular weight sodium polyacrylate is relatively low, the molecular chain is shorter, and the formed colloidal structure is not as good as modified polyacrylamide. In addition to having a longer molecular chain and being able to form a stable colloidal structure in the slag, the modified polyacrylamide can also further enhance the colloidal structure through cross-linking reaction, thereby enhancing the cohesion and stability of the slag. Therefore, when part of the hydrolyzed polyacrylamide is replaced by a 5000 molecular weight sodium polyacrylate aqueous solution, the improvement effect of the slag becomes worse.

[0050] In summary, in the slag conditioners for different geological conditions, different concentrations of modified polyacrylamide will affect the modification effect. In pure sand formations, a slag conditioner for shield construction prepared in Example 1 has the best performance. In sand and gravel formations, a slag conditioner for shield construction prepared in Example 4 has the best performance. In mudstone formations, a slag conditioner for shield construction prepared in Example 9 has the best performance. In composite formations, a slag conditioner for shield construction prepared in Example 12 has the best performance.

[0051] In summary, the adhesion to the slag is further enhanced by cross-linking partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol, thereby improving the overall stability and shear strength of the slag. The hydrophilic group is used to further improve the water retention rate of the slag. The tight network structure reduces the permeability of the slag. The low-concentration modified polyacrylamide can effectively improve its uniform distribution in the slag. Combined with the balanced technology of precise pressure maintenance in the soil bin, mud injection in the middle shield, simultaneous injection of thickened plastic dual-liquid slurry, and multi-sequence grouting, micro-settlement control during shield construction can be achieved.

[0052] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A slag improver for shield construction, characterized in that: The invention comprises the following components: 50-100 parts by weight of modified polyacrylamide, 0.4-0.6 parts by weight of foaming agent and 800-1000 parts by weight of water; The modified polyacrylamide is obtained by modifying partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol in a mass ratio of 1:0.3-0.

7.

2. The slag improver for shield construction according to claim 1, characterized in that: The preparation method of the modified polyacrylamide is as follows: The partially hydrolyzed polyacrylamide and dihydrodehydroconiferyl alcohol are dissolved in dimethyl sulfoxide respectively, and stirred until completely dissolved to form a uniform solution. In the solution containing the partially hydrolyzed polyacrylamide, the pH value is adjusted to 6-7, and a catalyst p-toluenesulfonic acid is added, and then N,N'-carbonyldiimidazole is added. After stirring evenly, the solution containing dihydrodehydroconiferyl alcohol is added to the solution containing the partially hydrolyzed polyacrylamide, and stirring is continued. At 40-60°C, stirring is continued and the constant temperature is maintained for 4-8h. The mixed solution after the reaction is poured into a large amount of deionized water, filtered, washed and dried to obtain modified polyacrylamide.

3. The slag improver for shield construction according to claim 2, characterized in that: The mass concentration of the solution containing partially hydrolyzed polyacrylamide is 5-10%, and the mass concentration of the solution containing dihydrodehydrodisinopyrrol is 1-4%.

4. The slag improver for shield construction according to claim 2, characterized in that: The mass fraction of the toluenesulfonic acid in the solution containing partially hydrolyzed polyacrylamide is 0.1-0.5%, and the mass fraction of the N,N'-carbonyldiimidazole in the solution containing partially hydrolyzed polyacrylamide is 1-2%.

5. The slag improver for shield construction according to claim 2, characterized in that: The partially hydrolyzed polyacrylamide has a hydrolysis degree of 35-40% and a molecular weight of 12-16 million.

6. The slag improver for shield construction according to claim 1, characterized in that: The slag improver is prepared by mixing a foaming agent with a low-concentration modified polyacrylamide solution, wherein the foaming agent is mixed with a modified polyacrylamide solution with a mass fraction of 5-10% in a mass ratio of 0.4-0.6:1000, and the optimal slump of the slag improvement is 10-15 cm.

7. The slag improver for shield construction according to claim 1, characterized in that: The injection volume of the soil conditioner accounts for 1-3% of the volume of the different geological soils to be improved, and the different geological soils to be improved are one or more of pure sand formations, sand and gravel formations, mudstone formations and composite formations.

8. A method for controlling the settlement of a slag improver for shield construction, used for preparing a slag improver for shield construction as claimed in any one of claims 1 to 6, characterized in that: The steps include: Slag improvement: According to geological conditions and test data, adjust the proportion of components in the slag improver, inject the prepared slag improver into the front of the shield machine cutter head and the soil bin through a plunger pump, and the slag improver and slag are fully mixed under the action of the cutter head rotation and the screw conveyor to improve the slag performance; Precise pressure maintenance in soil bin: Use sensors to monitor pressure changes in the soil bin in real time, and dynamically adjust the pressure in the soil bin according to the shape of the excavation surface and the characteristics of the stratum to ensure that it remains between the active balance pressure and the passive balance pressure; Middle shield mud injection: During the shield tunneling process, start the mud injection pump to inject plastic mud into the gap formed by the shield body and the excavation forming surface. To prevent the loss of plastic mud, keep the pressure difference between the synchronous grouting pressure and the soil bin pressure below 0.15MPa; Synchronous injection of thickened plastic dual-liquid slurry: During the shield tunneling process, the dual-liquid slurry grouting pump is started to inject thickened plastic dual-liquid slurry into the gap between the segment and the stratum; Multi-sequence grouting: grouting is carried out every 12-24 hours after the installation of the pipe segment. The grouting locations are the gaps left after the initial construction and the unsatisfactory areas caused by water loss during the solidification process of the synchronous thickening plastic double liquid slurry. The grouting ratio is a water-cement ratio of 1:0.5~1, and the grouting pressure is 3-4bar.

9. The method for controlling the settlement of a slag improver in shield construction according to claim 8, characterized in that: The plastic mud is prepared by using calcium-based bentonite: water: water glass in a mass ratio of 15-20:10-15:

1.

10. The method for controlling the settlement of a slag improver in shield construction according to claim 8, characterized in that: The thickened plastic double liquid slurry is prepared by mixing liquid A and liquid B in a volume ratio of 10:1-3, wherein the liquid A is prepared by 150-200 parts by weight of cement, 350-400 parts by weight of fly ash, 650-700 parts by weight of dry fine sand, 50-100 parts by weight of sodium bentonite and 400-450 parts by weight of water, and the liquid B is prepared by mixing 5-6 parts by weight of polyacrylamide and 994-995 parts by weight of water.

Citation Information

Patent Citations

  • Subway engineering soft soil stratum earth pressure balance shield construction method

    CN112855188A